Stimulation of Hatching Efficiency in Capsulated Cysts of Artemia fransiscana Using 890 nm Diode Laser (Baghdad Science Journal, 2025)
Artemia fransiscana is one of the most important live food for commercial larval aquaculture. The aim of this study is to investigate the effects of 890 nm diode laser irradiation on Artemia capsulated cysts using (1-10) minutes exposure time, and 2.26x10-3 J/cm2 Fluence. The Artemia samples were obtained from two locations: Dyalaa and Basraa. After irradiation, hatching percentage (H %) and hatching efficiency(HE) of Artemia were measured after 24 and 48 hours of incubation. The results of the effect of laser light on the capsulated cysts from Dyalaa showed that the optimum dose for enhancing (H %) after 24 hours of incubation is using 10 minutes exposure time, while after 48 hours of incubation the (H %) enhancement can be achieved using 6 minutes exposure time. The optimum exposure times for (HE) enhancement after 24 and 48 hours of incubation were 5 and 7 minutes. The results of the effect of laser light on the capsulated cysts from Basraa showed that after 24 hours of incubation, the optimum exposure times for enhancement (H%) was 9 minutes, while after 48 hours of irradiation the best exposure times was 5 minutes .Very effective enhancement of (HE) was noticed after 24 hours of irradiation at 3 minutes exposure time using 2.26x10-3 J/cm2 Fluence. No enhancement was observed after 48 hours of irradiationIn conclusion, 890 nm diode laser irradiation can be used successfully for increasing Hatching percentage (H %) and Hatching Efficiency (HE) of Artemia capsulated cysts using certain energy density and certain exposure times